2013 IEEE International Electron Devices Meeting 2013
DOI: 10.1109/iedm.2013.6724721
|View full text |Cite
|
Sign up to set email alerts
|

Conductive-bridge memory (CBRAM) with excellent high-temperature retention

Abstract: High-temperature data retention is a critical hurdle for the commercialization of emerging nonvolatile memories. For Conductive-Bridge RAM (CBRAM) [1], we discuss hightemperature retention in terms of the physics of quantum point contacts, and we report on a family of CBRAM cells that achieve excellent retention at temperatures exceeding 200ºC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…This is achieved by changing the Fermi wavelength of the CF material by semiconductors doping. Jameson et al [36] demonstrated improved stability of the CF and enabled the usage of LRS resistances showing lower conductance as compared to the pure metallic case. One clear advantage of this approach is the reduced operative power on large arrays without compromise in CF stability.…”
Section: Device Optimizationmentioning
confidence: 98%
See 1 more Smart Citation
“…This is achieved by changing the Fermi wavelength of the CF material by semiconductors doping. Jameson et al [36] demonstrated improved stability of the CF and enabled the usage of LRS resistances showing lower conductance as compared to the pure metallic case. One clear advantage of this approach is the reduced operative power on large arrays without compromise in CF stability.…”
Section: Device Optimizationmentioning
confidence: 98%
“…Aratani et al [56] presented four-level operation for a 20-nm scaled device structure with 10 7 cycles endurance. Finally, Jameson et al [36] presented a 1 Mb array structure integrated in 1T1R showing 10 ns fast pulse operation with 1000 hours retention at 200…”
Section: Device Optimizationmentioning
confidence: 98%
“…High temperature retention due to random diffusion of Ag or Cu atoms in the insulator has historically been considered a moderate weakness for EMB ReRAM. However, recent results show excellent retention, with states holding after 1000 h at 200°C [19]. Scalability to dimensions of 20 nm has been demonstrated for a GeSe EMB cell [20].…”
Section: Electrochemical Metallization Bridgementioning
confidence: 99%
“…13 An attraction is that memory based on structural changes should be non-volatile: ON-state data retention in PMC is estimated to be >10 yrs at room temperature; 8 and recently retention up to 10 5 minutes at 200 • C has been demonstrated for Ge-S-based PMC. 14 On the other hand, damage accumulation can limit the endurance; beyond 10 11 cycles is claimed with 20% decrease in ON current after 10 16 cycles. 15 PMC memory is highly scalable, including 3-D porous alumina templating.…”
Section: Introductionmentioning
confidence: 99%